Ferrocene anchored activated carbon as a versatile catalyst for the synthesis of 1, 5-benzodiazepines via one-pot environmentally benign conditions. Issue 23 (17th May 2022) - Kusuma, Suman; Patil, Komal N.; Srinivasappa, Puneethkumar M.; Chaudhari, Nitin; Soni, Ajay; Nabgan, Walid; Jadhav, Arvind H.
Abstract : 1, 5-Benzodiazepine is considered as one of the central moieties in the core unit of most drug molecules. Abstract : 1, 5-Benzodiazepine is considered as one of the central moieties in the core unit of most drug molecules. Construction of such moieties with a new C–N bond under solvent-free and mild reaction conditions is challenging. Herein, we present a benign protocol for one pot synthesis of 1, 5-benzodiazepine derivatives by using ferrocene (FC) supported activated carbon (AC) as a heterogeneous catalyst. The catalyst FC/AC was characterized by several analytical and spectroscopic techniques to reveal its physicochemical properties and for structural confirmation. The synthesized catalyst FC/AC was explored for its catalytic activity in the synthesis of 1, 5-benzodiazepines through condensation of o -phenylenediamine (OPDA) and ketones (aromatic and aliphatic) under solvent-free conditions. The robust 10 wt% FC/AC catalyst demonstrated appreciable activity with 99% conversion of diamines and 91% selectivity towards the synthesis of the desired benzodiazepine derivatives under solvent-free conditions at 90 °C in 8 h. Additionally, several reaction parameters such as catalyst loading, reaction temperature, effect of reaction time and effect of different solvents on selectivity were also studied and discussed in-depth. To understand the scope of the reaction, several symmetrical and unsymmetrical ketones along with different substituted diamines were tested with the synthesized catalyst. All prepared reaction products were obtained in good to efficient yields and were isolated and identified as 1, 5-benzodiazepines and no side products were observed. The obtained catalyst characterization data and the activity studies suggested that, the synergetic effect occurred due to the uniform dispersion of ferrocene over the AC surface with numerous acidic sites which triggered the reaction of diamine and ketone to form the corresponding benzodiazepine derivative and the same was illustrated in the plausible mechanism. Furthermore, the synthesized catalyst was tested for leaching and recyclability, and the results confirmed that catalyst can be used for up to six consecutive cycles without much loss in the catalytic activity and its morphology which makes the process sustainable and economical for scale-up production. The present method offered several advantages such as an ecofriendly method, excellent yields, sustainable catalytic transformation, easy work-up and isolation of products, and quick recovery of catalyst.